MORPHOMETRIC, PRODUCTIVE AND REPRODUCTIVE TRAITS IN INDIGENOUS CATTLE OF NORTHERN AZAD JAMMU & KASHMIR - B. Shahid; K. Z. Abbasi; M. I. Khan; F. S. Awan (Journal of Animal and Plant Sciences, 2022)
The objective of this research was to study the morphometric measurements, productive and reproductive performances of indigenous cows and heifers in Northern Azad Jammu & Kashmir (AJ&K). A total 237 phenotypic characteristics was recorded visually. Five main coat colors (reddish brown, light brown, black, white and grey) were found with black muzzle and eye-lashes. The head length was 37.7±0.2 cm with small horns (11±0.3 cm). The positive correlation between horn length/horn base circumference, ear length/ear width, forehead width/horn length were found statistically significant (p≤0.01). The highest positive correlations were found between age/rump width (0.77), age/parity (0.66), body weight/ heart girth (0.62) and parity/rump width (0.60). The average age at puberty (41.02±0.6 months), average age at first service (49.3±0.7 months), age at first calving (58.54±0.7 months), mean gestation period (279.6±0.2 days), mean post-partum heat period (253.2±14.8 days), mean service period (257.69±5.8 days), mean calving interval (17.87±0.4 months), mean service per conception (1.5±0.06) and average milk yield per day (1.20±0.06 litre) were also recorded. In conclusion, the indigenous cattle are short stature, reddish brown in color with poor reproductive and productive performance.
Keywords: Morphometric; Productive; Reproductive; Indigenous cattle; Azad Kashmir